VARIABILITY OF RIVER DISCHARGE AND ATLANTIC-WATER INFLOW AT THE LAPTEV SEA CONTINENTAL MARGIN DURING THE PAST 15,000 YEARS: IMPLICATIONS FROM MACERAL AND BIOMARKER PRODUCTS - Boucsein B.; Fahl K.; Stein R. (My University, 2000)
In order to reconstruct the depositional environment from the Laptev Sea continental slope and shelf during the past ~15,000 years BP maceral analysis was carried out on two sediment cores (PS2458-4, PS2725-5) and compared with organic-geochemical parameters. During the transition from the Last Glacial to the Holocene the environment of the Laptev Sea shelf was controlled by the post-glacial sea level rise, variations in river discharge, surface-water productivity, and Atlantic-water inflow along the Eurasian continental margin. Based on our results, we identify the following significant changes of the environment: (a) at approximately 13,500 years BP the first step of deglaciation (Termination 1a) is documented by the deposition of marine and fresh-water organic matter; (b) at approximately 10,400 years BP the first post-glacial influence of Atlantic-water inflow along the Eastern Laptev Sea continental margin is indicated by an increase in marine organic matter; (c) at the beginning of the Holocene an increased fluvial supply is documented by an increase in fresh-water alginite; and (d) since ~9500-8000 years BP modern marine conditions are established at the Laptev Sea continental margin as documented in increased amounts of marine macerals, biomarkers (dinosterol, brassicasterol, short-chain fatty acids), and dinoflagellate cysts.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен